The origins of morality : an evolutionary account - Krebs, Dennis (New York ; Oxford : Oxford University Press, 2011)
Why do people behave in moral ways in some circumstances, but not in others? In order to account fully for morality, Dennis Krebs departs from traditional approaches to morality that suggest that children acquire morals through socialization, cultural indoctrination, and moral reasoning. He suggests that such approaches can be subsumed, refined, and revised gainfully within an evolutionary framework.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Ethics, Evolutionary; Evolutionary psychology